KETAHANAN BEBERAPA VARIETAS TOMAT TERHADAP PENYAKIT Fusarium oxysporum DENGAN PEMBERIAN Trichoderma sp. - Sopialena . (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2015)
Fusarium wilt caused by Fusarium oxysporum .F. oxysporum including soil-borne diseases because it can survive in the soil in the form of klamidiospora,.  This fungus is relatively difficult to separate the soil. One technique is to use a control that disease-resistant varieties.  Some tomato varieties are known to have different resistance to fusarium wilt.  Some of these varieties are expected to break the life cycle of disease in the field.  The use of antagonistic fungi Trichoderma sp. can be hiperparasit on several species of fungi that cause plant diseases, growing very fast, and not become a disease of higher plants.  Trichoderma sp. naturally a parasite that many types of fungi attack the plant destroyer (broad spectrum control) and is a fungus that is involved in the natural competition among fungi.